Pre-harvest and pulse treatments of spermine, γ- and β-aminobutyric acid increased antioxidant activities and extended the vase life of gerbera cut flowers ‘Stanza’ - Mohammadi, Meisam; Aelaei, Mitra; Saidi, Mehdi (Ornamental Horticulture, 2020)
Capitulum wilting and neck bending are the two important complications that impair the post-harvest quality and vase life of the gerbera cut flowers. The present study investigates the effects of pre- and post-harvest treatments of spermine (SPER), γ-aminobutyric acid (GABA) and β-aminobutyric acid (BABA) on the vase life, qualitative features and enzyme activity of gerbera cut flowers ‘Stanza’. The pre-harvest treatments (1 mM doses) were applied by foliar spraying, and the post-harvest were by pulse treatment (5 mM doses). The flowers kept their quality longer in pre and post SPER and GABA treatments. The longest vase life was recorded in pre-SPER (14 days) and pre-GABA (13 days) compared to BABA treatments and controls (9 days). Neck bending was observed more frequently in controls whereas SPER and GABA showed a lower neck bending rate at 9 days after harvest. The highest vase solution uptake, total soluble solids, total flavonoid, total protein, the activities of catalase, peroxidase, superoxide dismutase, phenylalanine ammonia-lyase, and ascorbate peroxidase, besides the lowest neck bending, electrolyte leakage, malondialdehyde, H2 O2 and polyphenol oxidase activity were observed in pre-SPER treatment and subsequently in pre-GABA. Pre- and post-harvest treatments with β-Aminobutyric acid (BABA) had no significant effects on cut flowers compared to SPER and GABA, although showed slightly better effects than water control. It is therefore suggested that pre-harvest treatment using SPER and GABA can improve the vase life and quality of gerbera cut flowers.